A Swiss army knife approach to DQ assessments. (19th July 2007) - Cotik, V.; Lujan, P.; Scotton, D.; Yankelevich, D.
The use of tools in data and information quality diagnosis and improvement projects is desirable to automate clerical tasks and in some cases it is mandatory to be effective. In this work we present a toolkit that we developed in the context of the NEAT methodology, that provides a systematic way of assessing Data Quality. The novelty of the proposal is given by the construction of many independent single-purpose tools, which are combined into a powerful kit, and its insertion in the context of a methodology that follows the best practices accepted in the community. We also present the outcome of its use in actual projects.